2014
DOI: 10.1590/s0080-623420140000300018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stress factors and socio-demographic characteristics on the sleep quality of nursing students

Abstract: Few stress factors from the academic environment and some socio-demographic characteristics contributed to the reduction of sleep quality in students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
2
24

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 18 publications
7
44
2
24
Order By: Relevance
“…This result agrees with the results of a many other studies [5,19,20,24]. Our resealts revealed that most of the students (86.8%) who attended only <50% of the educational sessions were poor sleepers, which is in line with the results from Virginia, USA [28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result agrees with the results of a many other studies [5,19,20,24]. Our resealts revealed that most of the students (86.8%) who attended only <50% of the educational sessions were poor sleepers, which is in line with the results from Virginia, USA [28].…”
Section: Discussionsupporting
confidence: 93%
“…Those participants may not adequatelly adapted to such high load after studying at secondary schools. Anxiety and the pressure of passing the first years of medical school might also play role [24]. This finding coincides with results of a stuy of Brick et al from California University, USA [15].…”
Section: Discussionsupporting
confidence: 88%
“…Ticona et al (9) estudiaron la influencia de los factores de estrés y de las características sociodemográficas en la calidad del sueño de estudiantes de enfermería, verificando el predominio de estrés de nivel muy alto en la gestión del tiempo en un 27,8%, en la formación profesional en un 30,5%, y de baja calidad de sueño en un 78,8%.…”
Section: Nivel De Estrésunclassified
“…A predominância de mulheres entre os estudantes de enfermagem é uma característica histórica e marcante, também evidenciada em outras pesquisa com estudantes de graduação em enfermagem (Benavente et al, 2014;Moura et al, 2016).…”
Section: Fatores Preditores Do Desempenho Acadêmico Dos Estudantes Deunclassified
“…Em outros estudos o domínio ambiente não representou fator de estresse para os estudantes de enfermagem (Fernandes Pereira et al, 2014;Benavente et al, 2014). Em estudo com 149 estudantes de enfermagem do Paraná, o domínio ambiente, embora tenha representado baixo nível de estresse para os estudantes de enfermagem, 12,9% deles estavam em muito alto nível de estresse (Soares, Oliveira, 2013).…”
Section: Fatores De Estresse Em Estudantes De Enfermagemunclassified